Changing epidemiology of candidaemia in Australia. (8th November 2016) - Chapman, Belinda; Slavin, Monica; Marriott, Debbie; Halliday, Catriona; Kidd, Sarah; Arthur, Ian; Bak, Narin; Heath, Christopher H.; Kennedy, Karina; Morrissey, C. Orla; Sorrell, Tania C.; van Hal, Sebastian; et al.
Abstract : Objectives: Knowledge of contemporary epidemiology of candidaemia is essential. We aimed to identify changes since 2004 in incidence, species epidemiology and antifungal susceptibilities of Candida spp . causing candidaemia in Australia. Methods: These data were collected from nationwide active laboratory-based surveillance for candidaemia over 1 year (within 2014–2015). Isolate identification was by MALDI-TOF MS supplemented by DNA sequencing. Antifungal susceptibility testing was performed using Sensititre YeastOne™. Results: A total of 527 candidaemia episodes (yielding 548 isolates) were evaluable. The mean annual incidence was 2.41/10 5 population. The median patient age was 63 years (56% of cases occurred in males). Of 498 isolates with confirmed species identity, Candida albicans was the most common (44.4%) followed by Candida glabrata complex (26.7%) and Candida parapsilosis complex (16.5%). Uncommon Candida species comprised 25 (5%) isolates. Overall, C. albicans (>99%) and C. parapsilosis (98.8%) were fluconazole susceptible. However, 16.7% (4 of 24) of Candida tropicalis were fluconazole- and voriconazole-resistant and were non-WT to posaconazole. Of C. glabrata isolates, 6.8% were resistant/non-WT to azoles; only one isolate was classed as resistant to caspofungin (MIC of 0.5 mg/L) by CLSI criteria, but was micafungin and anidulafungin susceptible. There was no azole/echinocandin co-resistance. Conclusions: We report an almost 1.7-fold proportional increase in C. glabrata candidaemia (26.7% versus 16% in 2004) in Australia. Antifungal resistance was generally uncommon, but azole resistance (16.7% of isolates) amongst C. tropicalis may be emerging.